Helmet Use and Risk-Taking Behavior Among Skiers and Snowboarders. Issue 4 (July 2019) - Willick, Stuart E.; Wagner, Graham; Ericson, Don; Josten, George; Teramoto, Masaru; Davis, Jeremy
Abstract : Objective: To characterize factors associated with helmet use and risk-taking behavior among recreational skiers and snowboarders. Design: Observational study. Setting: Large, western United States mountain resort. Participants: 1285 male and female recreational skiers and snowboarders were interviewed during a single winter ski season. Independent Variables: Helmet use, demographic, and sport-related characteristics. Main Outcome Measures: Brief sensation seeking scale (BSSS) as a measure of risk-taking behavior and self-reported risk compensation. Results: Of the respondents (N = 1285), 17.5%, 12.5%, and 70.0% reported that they never, sometimes, and always wore a helmet, respectively. Multiple linear regression analysis showed that individuals reporting sometimes wearing a helmet had significantly higher BSSS scores than those reporting never wearing a helmet ( P = 0.031) or always wearing it ( P = 0.018). Male gender, younger age, snowboarding, higher perceived sport ability, more days per year skiing or snowboarding, and more time spent in the terrain park were significantly associated with higher BSSS scores ( P < 0.05). Logistic regression analysis focusing on subgroups of respondents who reported either sometimes or always wearing a helmet indicated that the odds of taking more risks when wearing a helmet for inconsistent helmet users was 75% higher than the odds for those who reported always wearing a helmet ( P = 0.06). Conclusions: Inconsistent helmet users have characteristics of risk-taking behavior and risk compensation. Male gender, younger age, snowboarding, higher perceived sport ability, and more time spent on the mountain and in the terrain park are also important determinants of risk-taking behavior.